Upaya Meningkatkan Aktivitas dan Hasil Belajar Fisika dengan Menerapkan Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) dengan Pendekatan Kontekstual - Edy Hariyanto (International Consortium of Education and Culture Research Studies, 2019)
This research is a Classroom Action Research about the application of STAD cooperative learning (Student Teams Achievement Divisions) with a contextual approach to increase student activity and learning outcomes. The research was conducted in 3 cycles of action. each cycle consisting of one meeting for 3 learning hours. The research subjects were students of class X MIPA-1 odd semester of the 2016-2017 academic year MA Ihyaul Ulum Dukun Gresik. Student learning activities are measured based on an increase in the average percentage of student learning activities, while student learning outcomes are based on the difference in scores between the pretest and post in each cycle. Based on the results of the study, it is known that the application of STAD cooperative learning with a contextual approach can increase activities and learning outcomes. Increased student learning activities are indicated by an increase in the average percentage of student learning activities and the level of success of actions from 55% (less) in the first cycle and in the second cycle increased to 67% (sufficient), and increased again in the third cycle to 75% (good ) While the increase in student learning outcomes based on the average score difference between pre-test and post-test in the first cycle of 28.7 increased to 34.1 in the second cycle and increased again to 34.6 in the third cycle, while the completeness of student learning in the cycle I amounted to 42% then in second cycle it increased to 62%, and increased again to 73% in third cycle.